Kahoot in formative evaluation: teaching experience in Higher Basic General Education - Quezada-Lozano, Grethy (2024)
The use of information and communication technologies (ICTs) has become widespread in today's society, covering various fields such as industry and communication. In the field of education, ICTs also play a fundamental role, since various multimedia tools and applications are used, such as videos, audio files, educational programs and didactic applications for pedagogical purposes. In this context, the use of Kahoot stands out as a teaching experience in Higher General Basic Education (EGB), specifically in formative assessment. The main objective of this research was to determine the impact of the application of Kahoot as a didactic strategy to assess knowledge in Natural Sciences. The research question was: Does the application of Kahoot have an impact on the learning of Natural Sciences? The methodology used in this study was quantitative, quasi-experimental, cross-sectional and descriptive. Two learning scenarios were considered: a traditional classroom (control group) and another in which the Kahoot evaluation tool was used (experimental group). The technique used to collect data was a survey applied to students through Google Forms. Among the main findings of this study, it is highlighted that the application of Kahoot as a didactic strategy for assessment significantly influences the levels of student participation in the learning of Natural Sciences.